Creating a sustainable future: insights into brand marketing in the luxury fashion industry - Harpreet Kaur; Shruti Choudhary; Adarsh Manoj; Muskan Tyagi (Cogent Business & Management, 2024)
This paper aims to develop a conceptual framework that elucidates the factors that impact sustainable luxury brand marketing, specifically focusing on the luxury fashion industry. The framework aims to highlight the role played by the industry in promoting economic, social, and environmental sustainability. By examining these factors, the study seeks to contribute to a better understanding of how luxury fashion brands can effectively incorporate sustainability into their marketing strategies, thereby fostering a more sustainable and responsible approach to luxury consumption. Applying the theoretical framework derived from the literature review and systematic mapping approach, we examine its relevance in the luxury fashion market. This exploration allows us to assess its practical applicability and gather empirical evidence regarding sustainable brand marketing in this context. This research will give an in-depth analysis of the major elements influencing the consumption of sustainable luxury goods. The findings expand our understanding of the sustainable practices adopted by luxury fashion brands, providing valuable insights for academia and the industry. This study's implications are profound: luxury brand managers can enhance brand value through insights on sustainable fashion consumption drivers, while sustainable brands gain strategies for audience engagement and loyalty.
Keywords: 650; Sustainability; luxury; branding; sustainable luxury fashion; sustainability challenges; purchase intention; attitude; fashion industry